Integration of Islam and Science Through the Recitation Learning Method: A Literature Review - Astutik, Aviyah Rini; Putri, Dita Melani; Masruroh, Meilatul; Alfariza, Syafira Alvina; Fauzi, Imron (Jurnal Penelitian Pendidikan Islam, 2022)
The recitation technique involves assigning homework to students to increase their grasp and knowledge of the material. The relationship between Islam and science can be viewed from various perspectives. Teachers have a crucial responsibility to help students comprehend how Islam and science are incorporated into one another to generate an adequate education. Consequently, a suitable approach is required. This study looked at integrating Islam and science using the recitation learning method. The method is a literature review that involves gathering a number of pertinent journal articles and books to conclude. The findings demonstrate that, in theory, Islam and science can be combined using the recitation learning approach. The integration of Islam and science is better understood by students using this teaching strategy.